Potensi Antidiabetes Ekstrak Metanol dan Fraksi dari Kulit Batang Chisocheton sp. (C.Dc) Harms pada Tikus Putih (Rattus norvegicus) (Sam Ratulangi University, 2024)
ABSTRACT The aim of this study was to determine the phenolic and flavonoid content and antidiabetic activity on glucose absorption in vitro and in white rats (Rattus norvegicus) from methanol extract and bark fractions of Chisocheton sp. (C. DC) Harms. Chisocheton sp bark powder. (C.DC) Harms are extracted using maceration and partition methods. The maceration yield of methanol extract was obtained at 12.50%. The highest partition yield was in the water fraction 15.42%, followed by the ethyl acetate fraction 11.66% and the lowest in the n-hexane fraction 8.80%. The highest phenolic content results were obtained from the methanol extract, 10.34 μg/mL, and the lowest was the n-hexane fraction, 2.39 μg/mL. The highest flavonoid content results were obtained from the methanol extract at 0.95 μg/mL and the lowest at the n-hexane fraction at 0.409 μg/mL. The results of glucose absorption in vitro showed that the water fraction had a higher glucose absorption capacity of 24.56% while the methanol extract had 10.97%. The results of antidiabetic activity testing in white rats (Rattus norvegicus) showed that there was a reduction in blood sugar levels after administration of methanol extract and water fraction at doses of (0.63 g/200gBW), (1.26 g/200gBW), and (2.52 g/200gBW). Based on this research, it can be concluded that extracts and fractions from the bark of Chisocheton sp. (C.DC) Harms has potential as an antidiabetic. Keywords: Bark of Chisocheton sp. (C.DC) Harms, glucose absorption, white rat (Rattus norvegicus), antidiabetic. ABSTRAK Tujuan penelitian ini adalah untuk menentukan kandungan fenolik dan flavonoid serta aktivitas antidiabetes pada penyerapan glukosa secara in vitro dan pada tikus putih (Rattus norvegicus) dari ekstrak metanol dan fraksi kulit batang Chisocheton sp. (C.DC) Harms. Serbuk kulit batang Chisocheton sp. (C.DC) Harms diekstraksi menggunakan metode maserasi dan partisi. Rendemen maserasi ekstrak metanol diperoleh 12,50%. Rendemen partisi tertinggi pada fraksi air 15,42%, diikuti oleh fraksi etil asetat 11,66% dan terendah pada fraksi n-heksana 8,80%. Hasil kandungan fenolik tertinggi diperoleh ekstrak metanol 10,34 μg/mL, dan terendah pada fraksi n-heksana 2,39 μg/mL. Hasil kandungan flavonoid tertinggi diperoleh ekstrak metanol 0,95 μg/mL dan terendah pada fraksi n-heksana 0,41 μg/mL. Hasil penyerapan glukosa secara in vitro menunjukkan bahwa fraksi air memiliki kemampuan penyerapan glukosa lebih tinggi 24,56% sedangkan ekstrak metanol 10,97%. Hasil pengujian aktivitas antidiabetes pada tikus putih (Rattus norvegicus) menunjukkan bahwa terdapat penurunan kadar gula darah setelah pemberian ekstrak metanol dan fraksi air dengan dosis (0,63 g/200gBB), (1,26 g/200gBB), dan (2,52 g/200gBB). Berdasarkan penelitian ini, dapat disimpulkan bahwa ekstrak dan fraksi dari kulit batang Chisocheton sp. (C.DC) Harms memiliki potensi sebagai antidiabetes. Kata Kunci: Kulit batang Chisocheton sp. (C.DC) Harms, penyerapan glukosa, tikus putih (Rattus norvegicus), antidiabetes.